HETEROLOGOUS EXPRESSION AND PURIFICATION OF RECOMBINANT PROAPOPTOTIC HUMAN PROTEIN SMAC/DIABLO WITH EGFP AS FUSION PARTNER - SALAMON, Pál; MIKLÓSSY, Ildikó; ALBERT, Beáta; KORODI, Mónika; NAGY, Katalin; BAKOS, Ildikó; LÁNYI, Szabolcs; ORBÁN, Csongor-Kálmán (Studia Universitatis Babeș-Bolyai Chemia, 2017)
New proteins as molecular targets in development of therapies are discovered every day. However, study of their interactions with other proteins or binding partners in complex cellular environments has its limits. Therefore, high-yield production of these proteins in heterologous systems is a valid necessity, while obtaining these proteins linked to suitable fluorescent markers represents a step ahead in protein-protein interaction studies and cellular or subcellular localization. In this study, we present production of human SMAC/Diablo recombinant protein with EGFP as a fusion partner. High-yield expression of the fusion protein was carried out in E. coli Rosetta™(DE3)pLysS strain, and an acceptable purity of the protein was obtained after affinity chromatography purification and gel filtration. The obtained protein can be further used in protein-protein interaction studies, whereas our method represents a cost-effective and efficient production method for EGFP-fused proteins, applicable for a number of therapeutically important polypeptides.